Contemporizing teaching case management: mapping the tensions. Issue 2 (17th February 2019) - Short, Monica; Trembath, Kay Susan; Duncombe, Rohena; Whitaker, Louise; Wiman, Gregory
ABSTRACT: Case management is experiencing a major evolution that involves the isolation of its roles and the compartmentalization of its functions. As educators, it is challenging to keep track of these changes and to equip students for contemporary practice. Five social work academics from three educational institutions undertook a co-operative inquiry into the research question; 'What are the tensions within the contemporary human and community services environment that are influencing the teaching of case management?' The inquiry examined the dominant tensions between social work case management and the contexts within case management is practiced. The shifting and shifty nature of case management and personalization approaches in the quasi-market emerged as key themes. Finally, we reflected on how our teaching practices equip students to deal credibly and courageously with the global and local trends that are currently influencing case management.